PENGARUH SUDUT PENGAPIAN DAN DURASI INJEKSI PENGGUNAAN ECU BERBASIS ARDUINO TERHADAP PERFORMA MOTOR 110CC FI - Tabah Muhamad Khadri; Taufik W. Saputra; Danar S. Wijayanto (Scientific Journal of Mechanical Engineering Kinematika, 2024)
The advancement of automotive technology in Indonesia has been rapid, particularly in motorcycle production, which reached 5,057,516 units in 2021 according to AISI data. Manufacturers now introduce models equipped with injection ignition systems using Electronic Control Units. These ECUs control actuators based on the inputs they receive. Arduino-based programmable ECUs are available to improve performance by adjusting ignition timing and fuel injection duration. This research aims to determine the impact of these adjustments on the torque, power, and fuel consumption of 110-cc FI motorcycle to find the best variations for optimal results. An experimental method was used, testing the Arduino-based programmable ECU against the standard ECU on 2014 Honda Vario 110-cc FI. Tests included variations in ignition timing of +20, +40, +60, +80, +100 degrees before TDC from the standard and fuel injection duration variations of +5%, +10%, and +15%. The highest torque was achieved with ignition timing variation of +40 degrees and injection duration of +5%, reaching 16.98 N.m. Maximum power was observed at +20 degrees timing and +10% injection, reaching 7.03 horsepower. Optimal fuel consumption was found at ignition timing of +20 degrees and injection duration of +5%, with rate of 4.15 ml/min, compared to the standard ECU.